2010
DOI: 10.1111/j.1532-5415.2010.03064.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Aggression Between Residents in Nursing Homes: Literature Synthesis of an Underrecognized Problem

Abstract: Evidence exists suggesting that most sexual aggression against older adults occurs in long-term care facilities. Fellow residents are the most common perpetrators, often due to inappropriate hypersexual behavior caused by dementing illness. This resident-to-resident sexual aggression (RRSA) is defined as sexual interactions between long-term care residents that in a community setting would likely be construed as unwelcome by at least one of the recipients and have high potential to cause physical or psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 79 publications
0
76
0
7
Order By: Relevance
“…Among these elderly individuals, inappropriate sexual behavior could be dealt with in very different ways depending on the jurisdiction. Sexual aggression within the nursing home setting is a relatively new issue that come to attention [56]. As with older offenders who commit general offences, older sexual offenders could be prosecuted criminally found incompetent to stand trial or not guilty by reason of insanity-though these outcomes may be less likely if a sexual offence is involved as there is often a Brational motive^(i.e., sexual gratification) for their offending.…”
Section: Aging and Sexual Offendingmentioning
confidence: 98%
See 1 more Smart Citation
“…Among these elderly individuals, inappropriate sexual behavior could be dealt with in very different ways depending on the jurisdiction. Sexual aggression within the nursing home setting is a relatively new issue that come to attention [56]. As with older offenders who commit general offences, older sexual offenders could be prosecuted criminally found incompetent to stand trial or not guilty by reason of insanity-though these outcomes may be less likely if a sexual offence is involved as there is often a Brational motive^(i.e., sexual gratification) for their offending.…”
Section: Aging and Sexual Offendingmentioning
confidence: 98%
“…Indeed, fronto-temporal dementias may disproportionately put an individual for criminal behavior including inappropriate sexual behavior [61,62]. There have also been a number of case studies of new onset inappropriate sexual behavior signaling the onset of new dementia [56,63,64]. Among elderly individuals referred for sexual behavior and mental health issues, the unrecognized prevalence of neurocognitive dysfunction was nearly 60 % [65•].…”
Section: Aging and Sexual Offendingmentioning
confidence: 99%
“…Still more recently, the works of Rosen and his colleagues that have drawn attention to RRA. (Rosen et al, 2010 and This author having consulted to long-term care facilities for over a decade has found that staff were much more attentive and more concerned about resident aggression toward staff than RRA. In discussions and training sessions with line staff in over one hundred nursing homes, when asked who is the greatest victim of resident aggression, their answer was staff.…”
Section: Essential Notes In Psychiatry 222mentioning
confidence: 99%
“…Similarly sexual violations range from a brief fondling to rape. (Rosen et al, 2010) This paper focuses on physical encounters. It should be remembered that the actual aggression spectru m r a n g e s f r o m y e l l i n g , v e r b a l a s s a u l t s , offensive gestures, pinching, throwing objects, hitting, punching, assaults to homicide .…”
Section: Types Of Rramentioning
confidence: 99%
“…Physical abuse of older people resident in nursing homes has been associated with cognitive and behavioural difficulties and previous victimisation. (2) Residents can also be at risk of abuse by other residents (16,17) .…”
Section: Introductionmentioning
confidence: 99%